O trabalhador do corte de cana no norte pioneiro do Paraná: o fim da atividade e os sentidos do trabalho - Rodrigues Filho, Luciano Ferreira (2015)
Sugar cane is part of the history of Brazil, and influence for social culture in the brazilian identity, was and is the raw material of important products for the country's economy, sugar and ethanol. However, in recent years, the cane fields of the country have been mechanized in harvesting and planting, resulting in decreased labor to cut sugar cane. This research aims to analyze the subjective dimensions and the meanings of work for cane cutting workers faced with the end of his activity in the Pioneer North of Paraná, where it applies to Resolution SEMA No. 076, of december 20, 2010 that provides for the "phasing out of straw removal of cane sugar by controlled burning" with this, the use of labor to cut sugar cane become unviable. Basing on the Socio-Historical Psychology, considering the subject is constituted in the dialectic relationship between the subject and the object, this research aims at understanding the subjective dimension, subjectivity - objectivity, for the constitution of cane cutting workers and thus understand the subject within a socio-historical context that changes. For this, outside held several conversations with rural workers, bookies, trade unionists and entrepreneurs to be able to know the determinants that mediate with the rural worker. Similarly, analyzing the socio-economic scenario of the country to understand the importance of sugar cane and the policy measures to the direction of workers and the production of sugar and ethanol. This made it possible to identify the end of the cane cutting activity occurred for the mechanization of sugarcane, but also by the current socio-economic context of the country that favors the migration of workers to other activities, however, the migration activity is not the end precarious work the sugarcane worker faces. The rural workers and their living conditions legitimized by capitalist ideology, are not as improvements to work, taking them to undergo other activities that pose risks to life and harms their health, thus, this dissertation contributes to clarify that the end a painful activity, does not guarantee improvements to the lives of workers in the same way that improvements in work conditions also are not guarantees of greater dignity at work, they often are camouflage mechanism and manipulate the expropriation of the worker